Protection of diplomats against terrorism under international law / Y. Muhammad Luwalira Lubowa - Y. Muhammad, Luwalira Lubowa (1996)
The duty to honour and protect officials of foreign embassies is of utmost importance and has been given due recognition for centuries. The main legal conventions dealing with the doctrine of the inviolability of foreign officials representing their countries as diplomats among others are The 1961 Vienna Convention On Diplomatic Relations, and The 1973 Convention On The Prevention And Punishment Of Crimes Against Internationally Protected Person, Including Diplomatic Agents.